THE ROLE OF MANAGEMENT IN INCREASING THE KNOWLEDGE OF PROSPECTIVE MUHAMMADIYAH SCHOLARS AT THE PESANTREN DARUL ARQAM MUHAMMADIYAH GOMBARA MAKASSAR - Kamaruddin (Adisam Publisher, 2025)
This study aims to explain the role of management in improving the knowledge of Muhammadiyah scholars in Darul Arqam Muhammadiyah Gombara Islamic Boarding School in Makassar and to find out the inhibiting and supporting factors. This research was conducted at Pesantren Darul Arqam Muhammadiyah Gombara Makassar by using a qualitative descriptive research approach with data collection techniques through observation and interviews and documentation with the management of the boarding and education fields or internal boarding schools. This research found that the management of Pesantren Darul Arqam Gombara towards increasing the knowledge of prospective Muhammadiyah Ulama was carried out through the process of planning, organising coaches, supervising and evaluating programs in accordance with the objectives of the pesantren in the form of a program to strengthen the basics of boarding knowledge for new students for three months which is packaged in the term Iddady Program including programs to develop basic Arabic language skills, practical worship, Tahsin and Tahfidz Al-Qur'an and akhlaq. The second is a routine boarding programme including advanced Arabic language learning, Muhadarah or speech practice, yellow book studies, advanced Qur'an Tahfidz and the Muballig Hijrah programme for final year students. There is a boarding report card that contains the competency achievements of the students which is submitted at the end of the semester. In the field of education, the school uses an integrated curriculum that combines the curriculum that has been published by the Education Office, the Ministry of Religion and the curriculum published by the Muhammadiyah Association in this case the Muhammadiyah Pesantren Development Institute (LP2M). The obstacles faced by pesantren management are influenced by the non-permanent resources of kemusyrifan or coaches which sometimes result in a vacuum of implementation and supervision which has an impact on the smooth running of pesantren programmes. Dormitory construction planning still needs to be improved and the construction is well pursued. Then the obstacles that also occur in the school education environment are the large number of core educators and education personnel who are appointed as civil servants / PP3K which results in them leaving the pesantren because they get a new place of assignment. Supporting factors are the great attention of the Muhammadiyah Regional leadership as the organiser of pesantren education in increasing the quantity and quality of pesantren resources and the number of students, which in recent years has increased thanks to the high public interest from year to year to enrol their children in this pesantren, especially from among Alumni and Muhammadiyah Association members.